A Narrative Inquiry of Student’s Academic Stress in English Subject - mohammad sofyan adi (International Journal of English Education and Linguistics (IJoEEL), 2023)
Academic stress is one of the things that are often experienced by students during the teaching and learning process, especially in English. This study aims to find out the factors that cause students academic stress in English subject. The research data was collected by distributing questionnaires to the tenth-grade students of SMA Nurul Jadid and interviewing three students in the superior language class of SMA Nurul Jadid who experienced academic stress high level. This study uses qualitative research, which uses a narrative inquiry approach. Based on the result findings and discussion in the previous chapter, the researcher concludes that there are three students in the tenth grade of SMA Nurul Jadid who experience academic stress in English subjects. The researcher found two factors that students in the tenth grade of superior language experienced academic stress, namely: internal factors and external factors. Internal factors include wrong mindset and low mentality. While the external factors are: busy class schedule, high achievement demand, and the friendship factor.